EVALUASI KEBIJAKAN PENGAWASAN PELEKATAN PITA CUKAI PADA MINUMAN MENGANDUNG ETIL ALKOHOL (MMEA) BUATAN DALAM NEGERI (Studi pada Kantor Pengawasan dan Pelayanan (KPPBC) Tipe Madya Cukai Malang) - PAM, DIO RAHADIAN (Jurnal Mahasiswa Perpajakan, 2015)
The domestic affairs Ethyl Alcohol Beverage production shows increasingly, makes Malang Office of Monitoring and Service Tax Excise Madya Cukai Type run faster for monitoring. The goal of this research is to know and evaluate the implementation of stamp excise agglutinative monitoring policy of domestic affairs Ethyl Alcohol Beverage, especially in Group B and Group C. Its analyzis based on William N. Dunn criteria model, those are effectiveness, eficiency, sufficiency, justicy, responsivity, and accuracy. This research also tries to explain and eveluate the supporting factors and the obstacle of its policy implementation. This is qualitative descriptive research. The primary datas by interviewing staff of Malang Office of Monitoring and Service Tax Excise Madya Cukai Type, Ethyl Alcohol Beverage producer and distributor, and also its consumers. Secondary datas come from some relevant documents. The research result shows that some of the criterias are done, like effectiveness, justicy, and responsivity. While the efficiency, sufficiency, and accuracy are not included. The supporting factors like from its good qualification employees, external aid, government support, and society support. The obstacles have a tendency from the minimum employees to do the task, and about low awarness of society or consumer. Keywords: Monitoring Policy, Stamp Excise Agglutinating, Domestic Affairs Ethyl Alcohol                        Beverage